2021
DOI: 10.1126/science.abj7781
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion and exploitation: The incarceration of Black Americans from slavery to the present

Abstract: Understanding long-run patterns in the incarceration of Black Americans requires integrating the study of racial inequality with the study of political economy. I offer a parsimonious framework describing how the Black incarceration rate has been affected by the dynamics of exploitation and exclusion over time and across space. This framework helps to explain otherwise puzzling facts, like why the Black incarceration rate was lower in the South than in the North for much of the 20th century, why it was lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Second, previously unidentified evidence that American Indians and Alaska Natives broadly face the greatest risk of imprisonment in the United States should encourage new thinking about the contours, causes, and consequences of mass incarceration. The sources of Black Americans’ unequal incarceration have been widely explored ( 23 , 24 ). Centuries of violence, enslavement, dispossession, segregation, and discrimination have predisposed contemporary criminal justice institutions against equal justice for Black people.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previously unidentified evidence that American Indians and Alaska Natives broadly face the greatest risk of imprisonment in the United States should encourage new thinking about the contours, causes, and consequences of mass incarceration. The sources of Black Americans’ unequal incarceration have been widely explored ( 23 , 24 ). Centuries of violence, enslavement, dispossession, segregation, and discrimination have predisposed contemporary criminal justice institutions against equal justice for Black people.…”
Section: Discussionmentioning
confidence: 99%
“…32–38, 119–126; Unnever & Gabbidon, 2011), forming a basic assumption of the model. Similarly, historically oriented research has examined the incarceration of Black Americans from slavery to the present (Muller, 2021) and how it shaped contemporary racial inequality in family structure and employment, with ramifying downstream consequences for children's development and criminal justice experiences (Jaynes, 2023). As we will return to, even though the empirical study of mechanisms linking early‐life contexts to later‐life contexts and individual development is an area ripe for future inquiry, it is beyond the scope of our empirical analyses.…”
Section: A Life‐course Model Of Racial Inequalities In Arrestmentioning
confidence: 99%
“…Looking specifically at mid‐life, Holloway and Varner (2021) found that Black mothers also experienced increased stress in response to difficult circumstances in the lives of their children (2021). Because Black families are more likely to experience a number of structural barriers linked to racism, such as economic hardship (Williams & Baker, 2021) or mass incarceration (Muller, 2021), Black mothers experience increased levels of stress surrounding their children. This heightened level of parenting stress for Black mothers is another unique stressor that cannot always be captured without an intersectional lens.…”
Section: Responses To Oppressionmentioning
confidence: 99%